Characterization of reference genes for qRT-PCR normalization in rice-field eel (Monopterus albus) to assess differences in embryonic developmental stages, the early development of immune organs, and cells infected with rhabdovirus. Issue 120 (January 2022) - Liu, Yuchen; Wu, Shuwang; Jiang, Nan; Liu, Wenzhi; Zhou, Yong; Zeng, Lingbing; Zhong, Qiwang; Li, Zhong; Fan, Yuding
Abstract: Quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) has become a popular technique to assess gene expression. Suitable reference genes are normally identified first to ensure accurate normalization. The aim of the present study was to select the most stable genes in embryonic developmental stages, the early development of immune organs, and cells infected with Chinese rice-field eel rhabdovirus (CrERV) of the rice-field eel (Monopterus albus ). Four reference genes, including those encoding 18S ribosomal RNA ( 18SrRNA ), beta actin ( β-actin ), elongation factor 1 alpha ( EF1ɑ ), and glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) were assessed using geNorm, NormFinder, BestKeeper, and RefFinder software. Analyses indicated the stability ranking was 18SrRNA > β-actin > GAPDH > EF1α in the embryonic stage, with 18SrRNA as the most stable reference gene. For immunity-related organs at different developmental stages, the order in the thymus was β-actin > GAPDH > EF1α > 18SrRNA, with β-actin as the most stable gene. In both spleen and kidney tissues, the rank order was EF1ɑ > GAPDH > β-actin > 18SrRNA, with EF1α as the most stable gene. Furthermore, in rice-field eel kidney (CrE-K) cells infected with CrERV, the ranking was EF1ɑ > β-actin > GAPDH > 18SrRNA, with EF1α as the most stable gene. The results for cells infected with CrERV were verified by testing signaling pathway genes catenin beta 1 ( CTNNB1 ) and NOTCH1 based on the above four genes after virus infection in CrE-K cells. This study laid the foundation for choosing suitable reference genes for immunity-related gene expression analysis in rice-field eel. Highlights: Selection of suitable reference genes is fundamental to ensure accurate normalization in qRT-PCR. Four reference genes（ 18SrRNA, β‑actin, EF1ɑ, and GAPDH ）were assessed using geNorm, NormFinder, BestKeeper, and RefFinder. The most stable reference genes were first identified in embryonic stages, immune organs, and cells in the rice-field eel. This study laid the foundation for choosing suitable reference genes for immunity expression analysis in rice-field eel.